PENGEMBANGAN MODUL KIMIA ORGANIK BAHAN ALAM BERBASIS RISET UNTUK MENSTIMULUS BERFIKIR KRITIS MAHASISWA - Nurhamidah; Dewi Handayani; Wiwit (ALOTROP, 2024)
Providing learning resources related to the use of natural resources and the environment around us is very necessary, so that the learning process in class is more active and interesting. This research aims to develop a natural product organic chemistry (KOBA) learning module based on research results on the use of natural product compounds, so that students are more motivated in learning. Research and Development (R&D) or development research uses the ADDIE development model which consists of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 24 seventh semester students of the 2023/2024 Bengkulu University FKIP Chemistry Education Undergraduate Study Program. Data collection techniques use expert validation questionnaire sheets and student response questionnaires and data analysis techniques use quantitative data analysis. The results of the research show that the validator's assessment of the developed module obtained an average score of 93.60%, which is included in the very valid category, while the results of student assessments of the developed module obtained an average of 93%, which is included in the very interesting category. Based on the results of the expert validation assessment questionnaire and student response questionnaire, it can be concluded that the module developed is very suitable for use as a learning resource in the learning process.